IDENTIFIKASI MASALAH TIDUR TERHADAP ANAK EPILEPSI - Putri, Novrita Riawan; Novayelinda, Riri; Amir, Yufitriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Sleep disorder occurs when someone does not get enough quality of sleep. The prevalence of sleep disorders in children with chronic diseases is higher, one of them is in children with epilepsy. This study aims to identify sleep problems in epileptic children in Arifin Achmad Hospital with a cross-sectional study design. The research sample was 38 children with epilepsy who were taken based on the inclusion criteria using purposive sampling technique. The measuring instrument used is the questionnaire The Sleep Disturbance Scale for Children (SDSC). The analysis used is descriptive analysis. The results of the study found that 25 respondents (65,8%) had generalized seizure type, 18 respondents (47,4%) took Phenytoin type of antiepileptic drugs, followed by 10 respondents (26,3%) with Valproate, and Carbamazepine by 5 respondents (13,2%). The results also found that 21 respondents (55,3%) experienced sleep disturbances with t scores >39. The most types of sleep disturbances were disorders of initiating and maintaining sleep with 20 respondents (52,6%) followed by sleep-wake transition disorders with 19 (50%) and sleep breathing disorders with 11 respondents (28,9%). Recommended for parents to fulfill childrenâs sleep need so that sleep problems can be reduced. Â Keywords: children, epilepsy, SDSC, sleep problems